Potential activity of Linezolid against SARS-CoV-2 using electronic and molecular docking study - Morgon, Nelson H.; Grandini, Giulia S. [UNESP]; Yoguim, Maurício I. [UNESP]; Porto, Caio M.; Santana, Lucas C.; Biswas, Srijit; de Souza, Aguinaldo R. [UNESP] (Springer Nature, 2021)
The crescent evolution of a global pandemic COVID-19 and its respiratory syndrome (SARS-Cov-2) has been a constant concern (Ghosh 2021; Khan et al. 2021; Alazmi and Motwalli 2020; Vargas et al. 2020). The absence of a proven and effective medication has compelled all the scientific community to search for a new drug. The use of known drugs is a faster way to develop new therapies. Molecular docking is a powerful tool (Gao et al. J Mol Model 10: 44–54, 2004; Singh et al. J Mol Model 18: 39–51, 2012; Schulz-Gasch and Stahl J Mol Model 9:47–57, 2003) to study the interaction of potential drugs with SARS-CoV-2, Alsalme et al. (2020) and Sanders et al. (2020) spike protein as a consequence the main goal of this article is to present the result of the study of an interaction between (R and S)-Linezolid with receptor-binding domain (RBD) of SARS-Cov-2 spike protein complexed with human Angiostensin-converting enzyme 2 (ACE2) (6vW1 - from PDB). The Linezolid enantiomers were optimized at B3LYP/6-311++G(2d,p) level of theory. Molecular docking of the system (S)-Linezolid⋯RBD⋯ACE2 and (R)-Linezolid⋯RBD⋯ACE2 was performed, the analysis was made using LigPlot+ and NCIplot software packages, to understand the intermolecular interactions. The UV-Vis and ECD of the complexes - (R and S)-Linezolid⋯RBD⋯ACE2 were performed in two layers with DFT/6-311++G(3df,2p) and DFT/6-31G(d), respectively. The results showed that only the (S)-Linezolid had a stable interaction with − 8.05 kcal.mol− 1, whereas all the R-enantiomeric configurations had positive values of binding energy. The (S)-Linezolid had the same interactions as in the (S)-Linezolid ⋯ Haluarcula morismortui Ribosomal system, where it is well-known the fact that the latter has biological activity. A specific interaction on the fluorine ring justified an attenuation on the ECD signal, in comparison to isolated species. Therefore, some biological activity of (S)-Linezolid with SARS-CoV-2 RBD was expected, indicated by the modification of its ECD signal and justified by a similar interaction in the S-Linezolid⋯Haluarcula marismortui Ribosomal system.
Keywords: Linezolid; Molecular docking; SARS-CoV-2